2016
DOI: 10.1371/journal.pone.0156433
|View full text |Cite
|
Sign up to set email alerts
|

Low Serum Creatine Kinase Level Predicts Mortality in Patients with a Chronic Kidney Disease

Abstract: BackgroundSerum creatine kinase (sCK) reflects CK activity from striated skeletal muscle. Muscle wasting is a risk factor for mortality in patients with chronic kidney disease (CKD). The aim of this study is to evaluate whether sCK is a predictor of mortality and end-stage renal disease (ESRD) in a CKD population.MethodsWe included 1801 non-dialysis-dependent CKD patients from the NephroTest cohort. We used time-fixed and time-dependent cause-specific Cox models to estimate hazard ratios (HRs) for the risk of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
2
16
0
Order By: Relevance
“…When the correlation of serum CK levels with BIA data in HD and PD patient group was examined in the present study, it was determined that they had a positive statistically significant correlation with the variables such as BMI, BFR, lean body mass and body muscle mass (p<0.001) and a negative statistically significant correlation with TBW (p<0.001) in both patient populations. In the literature, Flahault et al, (2016) assessed retrospectively 1801 chronic kidney patients not undergoing dialysis in their study, where they stated that serum CK level had a significant correlation with BMI and muscle mass and that it may reflect the nutritional situation (8). In the present study, it was revealed that serum CK level was correlated with the parameters in BIA method that has been increasingly used recently, which is compatible with the literature.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…When the correlation of serum CK levels with BIA data in HD and PD patient group was examined in the present study, it was determined that they had a positive statistically significant correlation with the variables such as BMI, BFR, lean body mass and body muscle mass (p<0.001) and a negative statistically significant correlation with TBW (p<0.001) in both patient populations. In the literature, Flahault et al, (2016) assessed retrospectively 1801 chronic kidney patients not undergoing dialysis in their study, where they stated that serum CK level had a significant correlation with BMI and muscle mass and that it may reflect the nutritional situation (8). In the present study, it was revealed that serum CK level was correlated with the parameters in BIA method that has been increasingly used recently, which is compatible with the literature.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, a positive statistically significant correlation was determined between serum CK levels and albumin in HD and PD patient groups (p<0.001). Similar to the present study, in their study Flahault et al, (2016) determined the existence of a positive statistically significant correlation between serum CK levels and albumin (8).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nevertheless, our study documented a possible overestimation of renal function by more than 20% with eGFR-Cr in about 19% of RA patients, which was likely attributable to the presence of myopenia/sarcopenia. Flahault et al (23) reported that low serum CK levels in CKD patients reflected loss of muscle mass and malnutrition and were associated with high mortality. In our study, low CK was found to be an independent factor relevant to Group A.…”
Section: Discussionmentioning
confidence: 99%
“…CK isoenzymes also play important roles directly related to the occurrence of various diseases. For instance, a low level of CK in serum is associated with an increased risk of death in chronic kidney disease [10] and a significant decrease in the serum ubiquitous CK-Mt activity in Parkinson's disease patients [11]. In infectious diseases, CK was detected as upregulated in severe acute respiratory syndrome (SARS) [12], and was also found to be increased in corona virus disease 2019 (COVID-19) [13].…”
Section: Introductionmentioning
confidence: 99%